Penggunaan Teknologi Robotik Dalam Penghasilan Komponen Sistem Binaan Berindustri (IBS) ke Arah Revolusi Industri 4.0 dalam Sektor Pembinaan - Md Arif, Mohamad Irwan Hafizy; Sarpin, Norliana; Omar, Roshartini; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2020)
The technological advances of today’s technology have changed the landscape of the industrial world. These changes have caused the industry to undergo Industrial Revolutions 1.0 until the Industrial Revolution 4.0. In this regard, the construction sector is also experiencing changes in the use of technology. Thus, IBS is seen as a pioneering project for the construction industry by adopting the use of robotic technology in its component production as a starting point in the Industrial Revolution 4.0 in the construction sector. However, at present, the rate of robotic applications in the production of IBS components is still low in the construction industry. Therefore, this study was conducted to achieve two objectives, namely, to identify barriers to adapting the use of robotic technology in the production of IBS components and to review the strategies that the industry can take to address the issues of adapting robotic use in producing IBS components in Malaysia. A quantitative method study was conducted to achieve the research objectives through the distribution of questionnaires to 110 IBS class G7 manufacturing companies in the state of Selangor through google Forms via email and WhatsApp application and finally a total of 49 responses were obtained for data analysis. The results of the study have shown that the main obstacle that often haunts IBS entrepreneurs is the construction sector environment that is accustomed to using conventional methods. While the strategy that can be taken by industry players to increase the use of robotic technology in the production of IBS is through R&D innovation. In conclusion, all parties need to play an important role in realizing the construction industry reaching the level of Industrial Revolution 4.0 in Malaysia.